2021
DOI: 10.21608/zumj.2021.92746.2329
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-223-3p, miRNA- 2909 and Cytokines Expression in COVID-19 Patients Treated with Ivermectin

Abstract: Background: The role of Ivermectin in improving the outcome of coronavirus disease of 2019 (COVID-19) symptoms was reported in several studies, while its effect on the pro-inflammatory cytokines triggering the cytokine storm is still not investigated. Method: This study aimed to investigate the role of Ivermectin on the proinflammatory cytokines in Covid-19 patients and correlated the results with the expression of miR-2909, miR-223-3p. Three hundred and twenty hospitalized patients with confirmed moderate-sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Over 40 peer-reviewed studies ( Table 1 ) have demonstrated studies on the effectiveness of IVM in SARS-CoV-2 infection ( Alam et al, 2020 ; Khan et al, 2020 ; Kishoria et al, 2020 ; Reaz et al, 2020 ; Abd-Elsalam et al, 2021 ; Ahmed et al, 2021 ; Ahsan et al, 2021 ; Aref et al, 2021 ; Behera et al, 2021 ; Cadegiani et al, 2021 ; Chaccour et al, 2021 ; Chahla et al, 2021 ; Chowdhury et al, 2021 ; Elalfy et al, 2021 ; Faisal et al, 2021 ; Ferreira et al, 2021 ; Hellwig and Maia, 2021 ; Krolewiecki et al, 2021 ; Lima-Morales et al, 2021 ; López-Medina et al, 2021 ; Mohan et al, 2021 ; Morgenstern et al, 2021 ; Mukarram, 2021 ; Okumuş et al, 2021 ; Podder et al, 2021 ; Rajter et al, 2021 ; Ravikirti et al, 2021 ; Rezk et al, 2021 ; Seet et al, 2021 ; Shahbaznejad et al, 2021 ; Shoumann et al, 2021 ; Abbas et al, 2022 ; Ascencio-Montiel et al, 2022 ; Babalola et al, 2022 ; Beltran Gonzalez et al, 2022 ; Buonfrate et al, 2022 ; Hazan et al, 2022a ; Kerr et al, 2022 ; Lim et al, 2022 ; Mayer et al, 2022 ; Mustafa et al, 2022 ; Ozer et al, 2022 ; Reis et al, 2022 ; Shimizu et al, 2022 ; Zubair et al, 2022 ), with over 80% of studies showing positive outcomes with IVM treatment. Overall, IVM has shown 60–85% improvement in outcomes, including mortality, ventilation, recovery, clearance, and hospital/ICU admissions.…”
Section: Introductionmentioning
confidence: 99%
“…Over 40 peer-reviewed studies ( Table 1 ) have demonstrated studies on the effectiveness of IVM in SARS-CoV-2 infection ( Alam et al, 2020 ; Khan et al, 2020 ; Kishoria et al, 2020 ; Reaz et al, 2020 ; Abd-Elsalam et al, 2021 ; Ahmed et al, 2021 ; Ahsan et al, 2021 ; Aref et al, 2021 ; Behera et al, 2021 ; Cadegiani et al, 2021 ; Chaccour et al, 2021 ; Chahla et al, 2021 ; Chowdhury et al, 2021 ; Elalfy et al, 2021 ; Faisal et al, 2021 ; Ferreira et al, 2021 ; Hellwig and Maia, 2021 ; Krolewiecki et al, 2021 ; Lima-Morales et al, 2021 ; López-Medina et al, 2021 ; Mohan et al, 2021 ; Morgenstern et al, 2021 ; Mukarram, 2021 ; Okumuş et al, 2021 ; Podder et al, 2021 ; Rajter et al, 2021 ; Ravikirti et al, 2021 ; Rezk et al, 2021 ; Seet et al, 2021 ; Shahbaznejad et al, 2021 ; Shoumann et al, 2021 ; Abbas et al, 2022 ; Ascencio-Montiel et al, 2022 ; Babalola et al, 2022 ; Beltran Gonzalez et al, 2022 ; Buonfrate et al, 2022 ; Hazan et al, 2022a ; Kerr et al, 2022 ; Lim et al, 2022 ; Mayer et al, 2022 ; Mustafa et al, 2022 ; Ozer et al, 2022 ; Reis et al, 2022 ; Shimizu et al, 2022 ; Zubair et al, 2022 ), with over 80% of studies showing positive outcomes with IVM treatment. Overall, IVM has shown 60–85% improvement in outcomes, including mortality, ventilation, recovery, clearance, and hospital/ICU admissions.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation conducted by Rezk et al evaluated the effectiveness of ivermectin in reducing the fatality percentage by influencing the expression profile of miR-2029, miR-233-3p, on a group of 300 COVID-19-infected hospitalized patients. This shows the marked correlation of miRNA with the COVID-19 existing therapy [73] . Studies have related the positive results from the COVID-19 RT-PCR test to changes in the miRNA profiles in nasal swabs, which could potentially classify the case self-reliantly [65] .…”
Section: Future Headways For the Development Of Mir-therapeuticsmentioning
confidence: 74%
“…
Fig. 2 SARS-CoV-2 encoded miRNAs present in human serum during COVID-19 infection [14] , [15] , [16] , [54] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] .
…”
Section: Mirnas As Therapeutic Biomarkermentioning
confidence: 99%
“…In a multi-center clinical trial, the mortality rate decreased by 15% only in hospitalized individuals receiving different doses of IVM and different administration routes, while those receiving HCQ did not [ 250 ]. Besides, an Egyptian study observed a decreased in IL-6 and IL-1 cytokines in COVID-19 patients treated with IVM, with a reduction in the mortality rate and the hospitalization time [ 251 ]. Conversely, studies conducted in Pakistan and China did not detect differences in mortality rate, inflammatory markers, time of hospitalization, time of resolution of symptoms and syndrome course in mild and severe COVID-19 subjects [ 252 , 253 ].…”
Section: Anthelmintic Drugs Against Sars-cov-2mentioning
confidence: 99%